Circulation and diagnostics of Puumala virus in Norway: nephropatia epidemica incidence and rodent population dynamics. Issue 8 (6th June 2017) - Milhano, Natacha; Korslund, Lars; Evander, Magnus; Ahlm, Clas; Vainio, Kirsti; Dudman, Susanne G.; Andreassen, Åshild
Abstract : Hantaviruses pose a public health concern worldwide causing haemorrhagic fever with renal syndrome (HFRS) and hantavirus pulmonary syndrome (HPS). Puumala virus (PUUV) is the most prevalent hantavirus in Central and Northern Europe, and causes a mild form of HFRS, also known as nephropathia epidemica (NE). In nature, the main host of PUUV is the bank vole ( Myodes glareolus ), and transmission to humans occurs through inhalation of aerosols from rodent excreta. Nephropathia epidemica is particularly prevalent in Nordic countries, however, few studies of PUUV have been performed in Norway. The aim of this study was to analyse the dynamics of PUUV in Norway and compare with bank vole population dynamics, and also to complement the current diagnostic methodology of NE in Norway. Our results showed a significant seasonal and geographical variation of NE, and a general parallel peak trend between bank vole population densities and human NE incidence. A real‐time and a nested PCR were successfully established as an invaluable diagnostic tool, with detection and sequencing of PUUV in a human serum sample for the first time in Norway. Phylogenetic analysis showed clustering of the obtained human sample with previous Norwegian bank vole isolates.